Respuesta :

Answer: g(-3) is 9 .

Step-by-step explanation:

So there are two functions  and  the first function says that to get the solution x has to be greater than 4   and -3 which is the input is not greater than 4  so you can't use that function to solve for g(-3).

using the second function , it says that  x has to be less or equal to 4. And -3 is indeed less than 4 so you have to use the second function to solve for g(-3)  

g(x) = -2x + 3     Input -3  and solve

g(-3) = -2(-3) + 3

g(-3) = 6 + 3

g(-3) = 9